An Analysis of Service Quality Dimension in Relation To Patient Satisffaction and Loyalty in The Emergency Department of Ciputra Hospital Surabaya - Octavia Djoenaydy, Helen; Utami, Christina Whidya (Dinasti International Journal of Education Management and Social Science, 2025)
Service quality is a crucial aspect in determining patient satisfaction and loyalty, particularly in the Emergency Department (ED), which serves as the frontline of a hospital. This study aims to evaluate the influence of the five service quality dimensions—tangibles, reliability, responsiveness, assurance, and empathy—on patient satisfaction and loyalty in the Emergency Department of Ciputra Hospital Surabaya. This study has a sample size of 84 respondents. The method in this research is quantitative, with analysis using Partial Least Square - Structural Equation Model (PLS-SEM). Data collection in this study used a research instrument in the form of a Google Form. This study shows that service quality has a positive and significant effect on loyalty in the emergency room of Ciputra Surabaya Hospital. Service quality has a positive and significant effect on satisfaction in the emergency room of Ciputra Surabaya Hospital. Satisfaction has a positive and significant effect on loyalty in the emergency room of Ciputra Surabaya Hospital. Service quality also has a positive and significant effect on loyalty in the emergency room of Ciputra Surabaya Hospital through satisfaction as a mediating variable.